Post‐bariatric surgery hidradenitis suppurativa: a new patient subset associated with malabsorption and micronutritional deficiencies. (1st April 2019) - Garcovich, S.; De Simone, C.; Giovanardi, G.; Robustelli, E.; Marzano, A. V.; Peris, K.
Summary: Background: Bariatric surgery (BS) represents the most effective treatment for morbid obesity and its related complications, potentially ameliorating chronic comorbid inflammatory skin conditions, such as psoriasis and hidradenitis suppurativa (HS). Weight‐loss interventions are strongly encouraged in patients with HS, but the resulting effect on the course of the disease has been poorly reported. Aim: To describe the effect of BS‐associated weight‐loss on the course of HS. Methods: This was a retrospective, descriptive study of a hospital‐based patient cohort with HS in order to investigate the relationship between exposure to a BS procedure and the HS disease course. Clinical characteristics and BS‐related outcomes were retrospectively analysed by chart review for identified cases. Laboratory parameters for selected micronutrients (levels of vitamin A, D and B12, plus zinc and iron) were re‐evaluated at a follow‐up visit in each post‐BS case. Typical patients with HS from the general cohort served as controls for the comparison of vitamin D and zinc serum levels. Results: Of 178 patients with HS, 12 patients with incident HS who had undergone a BS procedure were identified. A subset of patients ( n = 10) developed initial signs and symptoms of cutaneous suppuration after experiencing weight loss related to malabsorptive bariatric procedures. Post‐BS patients with HS presented multiple micronutritional deficiencies and insufficient responses to standard, first‐line antibiotic treatments. Of the micronutrients we selected for analysis, zinc was found to be at significantly lower serum levels in post‐BS patients with HS compared with typical patients with HS. Conclusions: Post‐BS HS may represent a new patient subset, requiring customized clinical management.